The role of food processing in the inflammatory potential of diet during pregnancy - Carolina Assis Silva; Izabela da Silva Santos; Nitin Shivappa; James R. Hebert; Lívia Castro Crivellenti; Daniela Saes Sartorelli (Universidade de São Paulo, 2019)
ABSTRACT The aim was to investigate the relationship between the energy contribution (E%) of foods according to the degree of industrial processing and the energy-adjusted dietary inflammatory index (E-DII) in pregnancy. Two 24-hour dietary recalls were obtained from each of the 784 pregnant women. Adjusted linear regression models allowed observing an inverse association between E-DII scores and E% from minimally processed foods β = -0.049 (95%CI -0.055- -0.042) and a direct association with the E% of ultra-processed foods β = 0.052 (95%CI 0.045-0.058), indicating a relationship between the dietary inflammatory potential and the degree of industrial processing of foods.